Divided we fall: clinicians and academic psychiatrists need to stand together. (October 2017) - Allison, Stephen; Bastiampillai, Tarun; Battersby, Malcolm
Objective: Psychiatry faces urgent problems requiring united action. These problems affect academic psychiatrists in the universities, and clinicians in publicly funded mental health services. Academic units are isolated and endangered, finding it difficult to recruit. They could benefit from closer relationships with public mental health services, in terms of recruitment, shared teaching and clinical research. However, mental health services are preoccupied with their own problems, particularly in relation to acute clinical demand. How can we stand together to improve academic units and clinical psychiatry? Conclusions: Clinicians and academic psychiatrists can stand together on important matters, but it takes initiatives from local leaders to overcome the structural barriers between health services and the universities. An example is given of united action by clinicians and academic psychiatrists to address a crisis within a state mental health system. First, psychiatrists undertook independent health services research that compared the state system with those in other Australian and international jurisdictions. The comparative data was used to generate solutions, which were presented at every level from ministerial offices through to service managers. Finally, psychiatrists took up joint academic and clinical leadership roles in the university and the mental health system. This united research-led approach turned around the crisis in the state mental health system.